Optimalisasi Pengelolaan Zakat dalam Program Palembang Pintar pada Baznas Kota Palembang - Annur, Saipul; Izzaya, Haikal; Ibrahim, Ibrahim (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the optimization of zakat management in the